HUBUNGAN ANTARA POLA MAKAN DAN KONDISI PENYERTA DENGAN PREVALENSI STROK PADA USIA DEWASA DI INDONESIA: ANALISIS DATA RISKESDAS 2018 - Ahmad Syauqy; Lydia Ratnadewi Wiragapa; Moesijanti Yudiarti Endang Soekatri; Fitrah Ernawati; Choirun Nissa; Fillah Fithra Dieny (PERSATUAN AHLI GIZI INDONESIA, 2023)
The prevalence of stroke tends to increase with age. Several risk factors for stroke including frequent unhealthy food patterns and having comorbidities would be analyzed. The study aimed to evaluate the association between food patterns and comorbidities with stroke among adults in Indonesia. This study utilized 2018 Indonesian Basic National Health Survey (Riskesdas) data with a cross-sectional design among 15,539 subjects aged ³45 in Indonesia. Data were taken using a food frequency questionnaire and a structured questionnaire. Logistic regression analysis was used to analyze food patterns and comorbidities with stroke. The results showed that frequent consumption of sugary drinks (OR: 1.389; 95% CI: 1.142-1.689), salty foods (OR: 1.936; 95% CI: 1.639-2.286), processed foods (OR: 1.694; 95% CI: 1.321-2.172), instant food (OR: 2,104; 95% CI: 1,771-2.498), fatty rich foods (OR: 2,139; 95% CI: 1,757-2,605), and grilled goods (OR: 1,473; 95% CI: 1,166-1,860), and low consumption of fruits (OR: 1.474; 95% CI: 1.164-1.865) and vegetables (OR: 1.358; 95% CI: 1.087-1.698) were significantly associated with an increased risk of stroke. Central obesity (OR:1.198; 95% CI:1.021-1.405), hypertension (OR:1.802; 95% CI:1.528-2.125), dyslipidemia (OR:1.187; 95% CI:1.012-1.392), and diabetes mellitus (OR:1.902; 95% CI:1.516-2.386) were significantly associated with an increased risk of stroke. Consumption of unhealthy food ≥3 times/week, consumption of less healthy food 5 servings/week, and having comorbidities increased risks of stroke among adults in Indonesia.Keywords: food patterns, comorbidities, adults, stroke ABSTRAK Prevalensi strok cenderung meningkat seiring bertambahnya usia. Beberapa faktor penyebab strok yaitu sering mengonsumsi makanan berisiko, kurang mengonsumsi buah dan sayur, serta memiliki kondisi penyerta. Penelitian ini bertujuan untuk menganalisis hubungan pola makan dan kondisi penyerta dengan prevalensi strok pada usia dewasa di Indonesia. Penelitian ini menggunakan data Riskesdas 2018 dengan desain cross-sectional pada 15.539 subjek berusia 45 tahun keatas di Indonesia. Pengumpulan data menggunakan food frequency questionnaire dan kuesioner terstruktur. Penelitian ini menggunakan analisis deskriptif, chi-square, independent t-test, serta regresi logistik. Sering mengonsumsi minuman manis (OR:1,389; 95% CI:1,142-1,689), makanan asin (OR:1,936; 95% CI:1,639-2,286), makanan olahan berpengawet (OR:1,694; 95% CI:1,321-2,172), makanan instan (OR:2,104; 95% CI:1,771-2,498), makanan berlemak (OR:2,139; 95% CI:1,757-2,605), dan makanan yang dibakar (OR:1,473; 95% CI:1,166-1,860), serta kurang mengonsumsi buah (OR:1,474; 95% CI:1,164-1,865) dan sayur (OR:1,358; 95% CI:1,087-1,698) berhubungan signifikan dengan peningkatan risiko strok. Obesitas sentral (OR:1,198; 95% CI:1,021-1,405), hipertensi (OR:1,802; 95% CI:1,528-2,125), dislipidemia (OR:1,187; 95% CI:1,012-1,392), diabetes melitus (OR:1,902; 95% CI:1,516-2,386) berhubungan signifikan dengan peningkatan risiko strok. Sering mengonsumsi makanan berlemak dan menderita diabetes melitus merupakan faktor risiko strok terbesar pada subjek. Konsumsi makanan berisiko ≥3 kali/minggu, konsumsi buah dan sayur 5 porsi/minggu, serta memiliki kondisi penyerta meningkatkan risiko strok pada dewasa di Indonesia.Kata kunci: pola makan, kondisi penyerta, dewasa, strok